The Impact Langgams Music Instrumental of Javanese Style to Reduce Anxiety and Labor Pain (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2021)
Anxiety is a psychological factor that contributes to labor pain. The prevalence of mothers who experience anxiety before labor is 10-50%. Intervention to reduce anxiety and increase relaxation by listening to music. The research purpose is to analyze labor anxiety and pain to the group given intervention Langgam, music instrumental of Javanese style, with midwifery care routine. The research method used by Randomized Controlled Trial Experimental is an experimental study using random procedure to allocate various research factors to the research subject, so only the chance factor places the research subject into the intervention or control groups. There are 60 research subjects, the primiparous mothers, in the labor phase in Surakarta Hospital from December 2nd, 2019 - February 27th, 2020, with simple random sampling. Data analysis by Mann Whitney test and independent simple T-test. Result: For anxiety level, there is a significant difference between Javanese style Instrumental music (mean: 33.9) and midwifery care routine (mean: 37.9) with p value = 0.000. For labor pain, there is a significant difference between Javanese style Instrumental music (mean: 64.83) and midwifery care routine (mean: 76.13) with p value = 0.000. Conclusion: Langgam Music Instrumental of Javanese Style can reduce labor anxiety and pain in primiparous mothers in the first phase of active labor.